Magnetic resonance spectral characterization of diffusion with chemical shift resolution - Lasič, Samo; Åslund, Ingrid; Topgaard, Daniel (Diffusion Fundamentals, 2009)
We present a modulated gradient spin-echo method (MGSE), which uses a train of sinusoidally shaped gradient pulses separated by 180-degree RF pulses. The RF pulses efficiently refocus chemical shifts and de-phasing due to susceptibility differences, resulting in undistorted, high-resolution diffusion weighted spectra. This allows for simultaneous spectral characterization of diffusion of several molecular components with different chemical shifts. Feasibility of the technique is demonstrated by following the diffusion of water, oil, and water-soluble salt in a highly concentrated water-in-oil emulsion.